2021
DOI: 10.3897/neobiota.67.63208
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of invasive alien species in Argentina: a first national synthesis

Abstract: Invasive alien species (IAS) affect natural ecosystems and services fundamental to human well-being, human health and economies. However, the economic costs associated with IAS have been less studied than other impacts. This information can be particularly important for developing countries such as Argentina, where monetary resources for invasion management are scarce and economic costs are more impactful. The present study provides the first analysis of the economic cost of IAS in Argentina at the national le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 52 publications
1
13
0
2
Order By: Relevance
“…Adelino et al (2021) found a higher accumulated cost than us for Brazil because they did not remove entries from the original InvaCost dataset (USD 105.5 billion vs. USD 76.8 billion). For the same reason, Duboscq-Carra et al (2021) found an accumulated cost USD 5.5 million higher than us for Argentina (USD 6,907.6 million vs. USD 6,902.1 million). Conversely, Ballesteros-Mejia et al (2021) found smaller costs for Ecuador because one of the entries with high economic impact was classified in their study as low reliability and therefore removed from the main analyses (USD 86.2 million vs. USD 604.9 million; see details at Ballesteros-Mejia et al 2021).…”
Section: General Patternsmentioning
confidence: 64%
“…Adelino et al (2021) found a higher accumulated cost than us for Brazil because they did not remove entries from the original InvaCost dataset (USD 105.5 billion vs. USD 76.8 billion). For the same reason, Duboscq-Carra et al (2021) found an accumulated cost USD 5.5 million higher than us for Argentina (USD 6,907.6 million vs. USD 6,902.1 million). Conversely, Ballesteros-Mejia et al (2021) found smaller costs for Ecuador because one of the entries with high economic impact was classified in their study as low reliability and therefore removed from the main analyses (USD 86.2 million vs. USD 604.9 million; see details at Ballesteros-Mejia et al 2021).…”
Section: General Patternsmentioning
confidence: 64%
“…First, we remained conservative here and used only highly reliable cost entries. Second, many existing costs are simply unknown, or unreported, because the scientific literature reporting the economic consequences of biological invasions is still in its infancy in France, as evidenced by the 3% of currently introduced or invasive species having cost entries in InvaCost in France (Diagne et al 2020b, Angulo et al 2020. Out of the 2,621 invasive species in total, the remaining 97% of species likely represent a very high additional cost, as shown by the high extrapolations derived for invasive alien species invading France but with known costs only outside France.…”
Section: Discussionmentioning
confidence: 99%
“…As cost entries were obtained from different years and currencies, all costs were standardised to a unique and common currency, i.e. 2017 equivalent US dollars (US$) using official market exchange rates and taking into account the inflation since the year of cost estimation (see Diagne et al 2020b for complete details about formulas and calculations associated with the cost standardisation, as well as Diagne et al 2020a for a detailed description of the different steps of the construction of the InvaCost database). The latest version of this updatable database (9,823 cost entries), along with all related details and associated information, is fully accessible and openly available online (version 3.0; https://doi.org/10.6084/m9.figshare.12668570).…”
Section: Data Collection Compilation and Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite most of the economic costs in Singapore being related to the control of invasive species and the costs of healthcare, it can be assumed that other damage or losses have not yet been estimated. For example, similarly data-poor studies found major costs for agriculture in Argentina or the UK (Duboscq-Carra et al 2021;Cuthbert et al 2021a) or forestry in Sweden (Haubrock et al 2021b). In each case, it seemed clear that these trends were driven by few records, suggesting that a richer cost record might, in each case, reveal costs for other activity sectors, substantially raising the overall estimates.…”
Section: Discussionmentioning
confidence: 99%